(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the context of globalization, liberalization and privatization in India, women entrepreneurship from the spectrum below paves the way for women to join in the main stream processes for their economic and social development. Women entrepreneurs play the role as agents of development and as well as beneficiaries of development.